Predicting support for collective action in the conflict between Turks and Kurds: perceived threat as a mediator of intergroup contact and social identity - Hewstone, M; Heath, A; Çakal, H; Güler, M (SAGE Publications, 2016)
Two studies investigated the role of perceived realistic and symbolic threats in predicting collective action tendencies, and in mediating effects of intergroup contact and social identity on collective action in the context of an intractable conflict. Extending earlier research on collective action, integrated threat theory, and intergroup contact theory, we tested whether realistic and symbolic threats would predict collective action tendencies and outgroup attitudes; and mediate the effects of intergroup contact and social identity on collective action tendencies and outgroup attitudes among the advantaged, Turks, and the disadvantaged, Kurds. Findings from both studies (Study 1, N = 289 Turks; Study 2, N = 209 Kurds) supported the predictive and mediating role of threats on collective action tendencies and outgroup attitudes. Overall findings suggest that advantaged and disadvantaged groups might not always have disparate psychologies regarding collective action and incorporating perceived threats as antecedents of collective action can help to explain collective action tendencies among both groups especially in conflictual contexts.